An approach for metadata extraction and transformation for various data sources using R programming language - Forat Falih Hasan; Muhamad Shahbani Abu Bakar (Institute of Advanced Engineering and Science, 2022)
The metadata system is the key system for sharing and transforming data between various information systems (ISs), and each database system has its own structure for storing and retrieving metadata information. Metadata information must be extracted for data transformation. Furthermore, these procedures were required to communicate with each type of database system and retrieve the stored metadata; these processes required much information and effort. To overcome the challenge of accessing and extracting metadata from any type of data source, a unifomed method must be developed and integrated into any organization's information systems. The semi-structured data extraction method (SeDEM) is a developed method that includes three main operations: logical structure operation, unique key operation, and relationships operation. Finally, the accurate information obtained using the SeDEM addressed data quality issues concerning the integrity and completeness of the data transformation.